Validade e confiabilidade do teste de Zulliger aplicação R-Otimizado em adultos brasileiros - Grazziotin, Jucelaine Bier Di Domenico (2023)
Psychological assessment plays a central role in the domains of empirical psychology to understand the characteristics of personality and can help people make movements that culminates in healthy behaviors throughout life. When responding to demands originating from human aging, in different contexts, and providing information for decision-making, psychological assessment procedures should focus on choosing instruments that presents a range of research that provides a solid scientific basis for the proposed use and interpretations of the tests. In this perspective, the general objective of this study was to verify the effect of using the Zulliger test with R-Optimized application in non-patient Brazilian adults. To respond to the proposed general objective, two empirical studies were carried out: The first production, chapter 3, aimed to compare the performance in the Zulliger test due to the optimization of the number of responses during application. This is a quantitative research, with 74 individuals between 18 and 59 years old, non-patients, male and female, with high school, professionals from merchandising stores, located in the city of Passo Fundo. The participants responded to the instruments at two different moments and with an interval of three months between the first and second application. In the first evaluation, a sociodemographic data form (FLDS) and Zulliger were administered using the Comprehensive System (ZSC), a non-Optimized application (March 2021 to January 2022). In the second assessment, the same participant responded again to the FLDS and then to the Zulliger with R-Optimized administration (June 2021 to April 2022). The analyzes indicated that of the 126 Zulliger variables listed in this study, 40 (32%) showed an increase significant when using the R-Optimized application. An increase of moderate magnitude was noted in the most common determinants (FQo, FQu, Fpuro, (2), A, Zf, 3r+(2) and Adjes) without there being a proportional increase in perceptual distortion or more pathological indicators (FQ-). The results point positively to the use of the Zulliger R-Optimized application, from 3 to 5 responses per card, totaling between 9 and 15 responses per protocol, as favorable in the quality of the proposed interpretations of the instrument. The second production, chapter 4, aimed to assess personality characteristics and interpersonal relationship skills over time. This is a quantitative, longitudinal study, carried out with 20 non-patient trade workers, aged 18 to 56 years, who answered a sociodemographic questionnaire, Social Skills Inventory (IHS2-Del Prette) and the ZSC test. The first evaluation (Test) took place from 2009 to 2019; the second evaluation (Retest) took place in 2021 (M=7.7 years; SD=3.8). There were no statistically significant differences (ANOVA) in the personality characteristics assessed (ICC 0.40 to 0.81) and interpersonal relationship skills remained good and excellent. Empirical studies contribute to the improvement and updates of the technical-scientific quality of the Zulliger for professional use through an R-optimized application procedure, which may enhance the quality of personality assessments and guide prevention and mental health care measures for the adult population; and to broaden the understanding of personality aspects in the human aging process